A mixing blade - Shamsudin, Rosnah; Wong, Chiew Chan (2012)
The present invention relates to a mixing blade (100) comprising: a rod (101) vertically connected to a motor, the rod (101) located at the center of a cylindrical tank (200); and a scrapping blade (103) mounted on the rod (101); characterized in that the scrapping blade (103) further comprising: a floor scraper (103a) and a wall scraper (103b). The above provision is advantageous as it mixes the materials effectively without having left behind the materials unmixed. The present invention avoids the accumulation of the materials on the wall or base of the tank or container.